Brand Love - Batra, Rajeev; Ahuvia, Aaron; Bagozzi, Richard P. (Journal of marketing, 2012)
Using a grounded theory approach, the authors investigate the nature and consequences of brand love. Arguing that research on brand love needs to be built on an understanding of how consumers actually experience this phenomenon, they conduct two qualitative studies to uncover the different elements ("features") of the consumer prototype of brand love. Then, they use structural equations modeling on survey data to explore how these elements can be modeled as both first-order and higher-order structural models. A higher-order model yields seven core elements: self-brand integration, passion-driven behaviors, positive emotional connection, long-term relationship, positive overall attitude valence, attitude certainty and confidence (strength), and anticipated separation distress. In addition to these seven core elements of brand love itself, the prototype includes quality beliefs as an antecedent of brand love and brand loyalty, word of mouth, and resistance to negative information as outcomes. Both the firstorder and higher-order brand love models predict loyalty, word of mouth, and resistance better, and provide a greater understanding, than an overall summary measure of brand love. The authors conclude by presenting theoretical and managerial implications.